Maximum summer temperatures predict the temperature adaptation of Arctic soil bacterial communities - Rijkers, Ruud; Dekker, Mark; Aerts, Rien; Weedon, James T. (Biogeosciences, 2023)
Rapid warming of the Arctic terrestrial region has the potential to increase soil decomposition rates and form a carbon-driven feedback to future climate change. For an accurate prediction of the role of soil microbes in these processes, it will be important to understand the temperature responses of soil bacterial communities and implement them into biogeochemical models. The temperature adaptation of soil bacterial communities for a large part of the Arctic region is unknown. We evaluated the current temperature adaption of soil bacterial communities from 12 sampling sites in the sub- to High Arctic region. Temperature adaptation differed substantially between the soil bacterial communities of these sites, with estimates of optimal growth temperature (Topt) ranging between 23.4 ± 0.5 and 34.1 ± 3.7 ° C. We evaluated possible statistical models for the prediction of the temperature adaption of soil bacterial communities based on different climate indices derived from soil temperature records or on bacterial community composition data. We found that highest daily average soil temperature was the best predictor for the Topt of the soil bacterial communities, increasing by 0.63 ° C ° C-1. We found no support for the prediction of temperature adaptation by regression tree analysis based on the relative abundance data of the most common bacterial species. Increasing summer temperatures will likely increase Topt of soil bacterial communities in the Arctic. Incorporating this mechanism into soil biogeochemical models and combining it with projections of soil temperature will help to reduce uncertainty in assessments of the vulnerability of soil carbon stocks in the Arctic.